ANALISIS KINERJA BIROKRASI PEMERINTAHAN DESA PADA PERANGKAT DESA PAREREJO KECAMATAN PURWODADI KABUPATEN PASURUAN JAWA TIMUR - Rossa Ilma Silfiah; Munawaroh; Aminullah (Halu Oleo University, 2023)
The purpose of this study was to determine the Performance Analysis Of Village Government Bureaucracies In The Development Of Parerejo Village, Purwodadi District, Pasuruan District, East Java. This study uses a descriptive qualitative research method. The results of this study are based on indicators in Agus Dwiyanto's theory (2006: 50) regarding the measurement of the performance of the public bureaucracy as follows: (1) the performance of the Parerejo Village Government Bureaucracy has fulfilled the Productivity aspect due to work achievements by maximizing massive organizational evaluation. (2) The performance of the Parerejo Village Bureaucracy has fulfilled the Service Quality aspect because it has SOP as a public service mechanism. (3) The performance of the Parerejo Village Bureaucracy has fulfilled the Responsiveness aspect because it makes community complaints material for organizational evaluation in improving the quality of performance. (4) The Bureaucratic Performance of Parerejo Village has fulfilled the Responsibility aspect because it opens the widest possible forum for public participation. (5) The performance of the Parerejo Village Bureaucracy has met the Accountability aspect because it opens a public participation forum through a Joint forum or media portal as a form of Village Government accountability to the Community.